MICROPROPAGATION OF PIMPINELLA CANDOLLEANA WIGHT & ARN. - AN ENDEMIC MEDICINAL HERB FROM SOUTH INDIA - A. SRILAKSHMI,; M.C. GAYATRI, (International Journal of Pharma and Bio Sciences, 2014)
Micropropagation protocol of Pimpinella candolleana an important ethno medicinal herb has been developed for the first time. High frequency plantlet regeneration was achieved from shoot tip explants of P. candolleana. Effect of growth regulators in different concentrations and combination of BAP, KN, NAA, IAA and IBA on in vitro morphogenesis was tried. The highest regeneration response was observed in Murashige and Skoog’s Basal Medium (MSBM) fortified with BAP (13.31µM) and NAA (2.69 µM) where 94 % of the cultures responded with an average set number of 7.20 ±. 0.81 per explant in six weeks time. The best elongation response was noticed on MSBM supplemented with BAP 13.31µM + GA3 1.44 µM where 93% of the shoots attained the average height of 6.80 ± 0.50. Rooting was achieved on half strength MSBM with 9.8 µM IBA. The plantlets with well developed shoot and root system were hardened and acclimatized to the natural habitat with 90% survival frequency.